Influencia de la estrategia didáctica “Comprendo mi texto” para mejorar los niveles de comprensión lectora de los alumnos del 3er grado de la I.E José Carlos Mariátegui - Quispe Alvitres, Denny (2014)
The research aims to determine the incidence of Teaching Strategy "1 understand my text" will improve reading comprehension levels of third grade students of School "José Carlos Mariátegui" Rupacucha sector of the province of Rioja, in the year 2011. The study is important because it helped to show that the teaching strategy "1 understand my text" has affected the reading comprehension levels. The central objective of the research was to demonstrate the influence of the teaching strategy "1 understand my text" in reading comprehension levels of third grade students of School "José Carlos Mariátegui" Rupacucha sector Rioja Province in the year 2011, and the specific objectives were to analyze the reading comprehension levels of third grade students of School "José Carlos Mariátegui" Rupacucha sector, applying the teaching strategy "1 understand my text" in reading comprehension levels of third grade students of School "José Carlos Mariátegui" Rupacucha sector, analyze the influence of the teaching strategy "1 understand my text" in reading comprehension levels of third grade students of School "Jase Carlos Maridtegui "Rupacucha sector. Reading comprehension levels is supported by Mary E. Camba, (2006) and Helver Guivar, Rosario Arriola and Miguel Urbiola (2011 ), the first author develops the literal, inferential, critica!, and second, addressing the level of appreciation and creative teaching strategy and "understand my text "is founded by lselda Elizondo (2000), Helver Guivar, Rosario Arriola and Miguel Urbiola (2011 ), who manage to make viable the strategy in its early stages and processes. The theoretical support referred to above, we propase the following hypothesis: The teaching strategy "1 understand my text" significantly improve reading comprehension levels of third grade students of School "José Carlos Mariátegui" Rupacucha sector Rioja Province, in 2011. Methodologically, the research design was pre-experimental, with a sample of 18 third graders (section only) primary education school "José Carlos Mariátegui" Rupacucha Sector Rioja city, in 2011. The results of the statistical analysis it was found that the hypothesis is accepted or research center obtained from .the probability table of t-distribution with a confidence level of 95%, and the calculated te = -12,39 and tabulated value of t1 = -1,74 verifying that the calculated value is less than the tabular value left, which · allows the null hypothesis to fall within the rejection region, accepting the research hypothesis, whereupon the application of the teaching strategy "1 understand my text "significantly improved reading comprehension levels of students in the third grade.